2004
DOI: 10.1007/s00467-003-1408-6
|View full text |Cite
|
Sign up to set email alerts
|

NPHS2 mutation associated with recurrence of proteinuria after transplantation

Abstract: Mutations in the NPHS2 gene encoding podocin are associated with steroid-resistant nephrotic syndrome (SRNS) in childhood. Patients usually present with focal segmental glomerulosclerosis (FSGS). It is unclear to what extent SRNS due to NPHS2 mutations predisposes to recurrence of proteinuria/FSGS after renal transplantation (RTx). A 4-year-old girl with infantile SRNS was started on peritoneal dialysis because of end-stage renal disease due to FSGS. Mutational screening of the patient and her parents revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 12 publications
2
34
0
1
Order By: Relevance
“…In addition, this individual developed recurrent proteinuria after transplantation, which responded to plasmapheresis. Although it is not clear why disease should recur in this individual's renal allograft (with a normal ACTN4 genotype), this is consistent with previously reported findings of posttransplantation disease recurrence in podocin-defective patients (17). We are not aware of the development of recurrent proteinuria or FSGS in any other case of ACTN4-associated disease.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, this individual developed recurrent proteinuria after transplantation, which responded to plasmapheresis. Although it is not clear why disease should recur in this individual's renal allograft (with a normal ACTN4 genotype), this is consistent with previously reported findings of posttransplantation disease recurrence in podocin-defective patients (17). We are not aware of the development of recurrent proteinuria or FSGS in any other case of ACTN4-associated disease.…”
Section: Discussionsupporting
confidence: 88%
“…The clinical differences in pathogenesis, response to treatment, and recurrence of disease after transplantation between genetic and nongenetic cases of primary FSGS have been a steady topic of discussion. 22,23 Carraro et al analyzed five patients with autosomal recessive steroid-resistant nephrotic syndrome (SRNS) (NPHS2) for serum glomerular permeability activity (Palb), and found high pretransplant Palb in all cases, equivalent to values observed in idiopathic FSGS. 24 In the PodoNet cohort, circulating suPAR levels were higher in familial FSGS and FSGS with documented NPHS2 mutations, and the difference remained significant after adjustment for other covariates.…”
Section: Discussionmentioning
confidence: 99%
“…As in our patient, attempts to demonstrate anti-podocin antibodies in both patients have not been successful. Billing et al [50] recently reported a 4.5-year-old girl with infantile steroid-resistant FSGS and a homozygous deletion in exon 8 of the NPHS2 gene who was transplanted with her mother's kidney. Significant proteinuria developed 1 week after transplantation and disappeared following methylprednisolone pulses, increased cyclosporine dosage, and ramipril.…”
Section: Recurrence Of Proteinuria Following Renal Transplantationmentioning
confidence: 97%